Formulation dan Phyical Stability Test Of Turi Leaf Extract (Sesbania grandiflora L.) Silver Nanoparticle Soap - Savitri, Astri Aulia; Amananti, Wilda; Santoso, Joko (Universitas Negeri Medan, 2024)
One metal that is widely researched is silver (Ag) which can be used as an antibacterial and antifungal. The method that is widely developed is the biological method, also called biosynthesis. Biosynthesis is a synthesis method using media from plant extracts. This research was conducted to determine the best formulation of Ag nanoparticle soap from turi (sesbania grandiflora) leaf extract based on its stability test. To obtain turi leaf extraction using the infusion method, a flavonoid compound test was carried out to determine the flavonoid compound content. After knowing the existence of flavonoid compounds, the wavelength was determined using UV-Vis Spectrophotometry. In the nanoparticle soap formula, a nanoparticle soap preparation was made which was then tested for the physical quality of Ag nanoparticle soap from turi leaf extract (Sesbania Grandiflora L). The gel-shaped preparation has a characteristic oleum rosae odor and a yellow to blackish soap color. Test the homogeneity to see if there are coarse grains on the surface of the soap. The specific gravity test results of all soap formulations meet the criteria for good soap. The high foam value in soap preparations is between 6.1 – 12.5 mM. The results of measuring the absorption values for concentrations of 1 mM, 2 mM, and 3 mM show that the optimum absorption results in liquid soap preparations are a concentration of 3 mM with a wavelength of 300 nm with an absorbance value of 1.105. The research results showed that turi leaf extract (sesbania grandiflora L) had an effect on the physical stability of Ag nanoparticle soap and met the standards set by SNI. Among formulation 1 with a concentration of 0.03, formulation II with a concentration of 0.06 and formulation III with a concentration of 0.09, the turi leaf extract soap preparation showed the best physical properties in formulation 1 with a concentration of 0.03 in the pH stability test.